2013
DOI: 10.1108/fs-05-2012-0036
|View full text |Cite
|
Sign up to set email alerts
|

Foresight of evolving security threats posed by emerging technologies

Abstract: Purpose -Many emerging technologies are being developed in an accelerating pace and are key drivers of future change. In foresight studies, usually their positive impact on the quality of life is considered or their negative environmental effects. This paper seeks to draw attention to an overlooked ''dark side'' of new technologies: their potential abuse by terrorists or organized crime. Recent cybercrime events are examples of abuse that perhaps could have been minimized if appropriate foresight studies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Three studies (Hauptman and Sharan, 2013 ; Fears and ter Meulen, 2018 ; Kirkpatrick et al, 2018 ) identified illegal gene editing in the context of dangerous pathogens (e.g., viruses). Hauptman et al refer to the increasingly accessible genetic engineering tools that can be used to make more virulent pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (Hauptman and Sharan, 2013 ; Fears and ter Meulen, 2018 ; Kirkpatrick et al, 2018 ) identified illegal gene editing in the context of dangerous pathogens (e.g., viruses). Hauptman et al refer to the increasingly accessible genetic engineering tools that can be used to make more virulent pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The review of recent academic literature on technological change and innovation as security threats revealed that the methods mostly used are foresight and expert surveys [e.g. [1][2][3][4][5]. The current state of development of science and technology, as well as the complexity and uncertainty surrounding the development require interdisciplinarity and imagination of the highest possible number of experts.…”
Section: Methods and Theory: Foresight Content Analysis And Securitmentioning
confidence: 99%
“…Recently, these issues were discussed in the World Economic Forum's (WEF) Global Risks Reports [4,5] and in the publications of the EU-funded project called Foresight of Evolving Security Threats Posed by Emerging Technologies (FESTOS) [e.g. [1][2][3].…”
Section: Technological Change and Innovation As Security Threats In Amentioning
confidence: 99%
“…In fact, [28] adds that implementation of AI in forecasting adds to the existing threats and also introduces new threats and advances threat characters. Also, AI-based forecasting is an emerging technology, and such technologies are being termed as prone to cyberthreats irrespective of how beneficial they are [29]. So, it is justifiable that AI-powered forecasting is prone to manipulation through cybercrime, which proves this hypothesis to be true.…”
Section: H7: Ai-based Forecasting Is Subject To Cyberattacksmentioning
confidence: 99%